2002
DOI: 10.1207/s15326969eco1403_3
|View full text |Cite
|
Sign up to set email alerts
|

Gibson's Affordances and Turing's Theory of Computation

Abstract: The concept of affordance is a central component of the ecological psychology of J.J.Gibson. Affordances are properties of the environment taken relative to an observer.Ecological theorists have developed formal models for the analysis of affordances. Models proposed by Shaw and Turvey (1981), Turvey (1992) and Greeno (1994) are described and evaluated and another approach, using Turing's theory of computation, is outlined.Affordances are characterised as the configurations of Turing machines. It is shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 23 publications
1
35
0
5
Order By: Relevance
“…Despite thus providing an elementary and pivotal formalism for the nature of affordances, we however argue that this relation does not capture the various aspects of affordances in full detail as discussed next. Recent research (Ellis & Tucker, 2000;Wells, 2002;Cisek, 2007;Borghi & Riggio, 2015) has shown that affordances-outside of their fundamentality and independence-are, further to that, of a hierarchical, competitive and dynamic nature. This requires an extension of the relational scheme as introduced by Chemero (2003).…”
Section: An Extended Definition Of Affordancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite thus providing an elementary and pivotal formalism for the nature of affordances, we however argue that this relation does not capture the various aspects of affordances in full detail as discussed next. Recent research (Ellis & Tucker, 2000;Wells, 2002;Cisek, 2007;Borghi & Riggio, 2015) has shown that affordances-outside of their fundamentality and independence-are, further to that, of a hierarchical, competitive and dynamic nature. This requires an extension of the relational scheme as introduced by Chemero (2003).…”
Section: An Extended Definition Of Affordancesmentioning
confidence: 99%
“…From a behavioral point of view, these interrelations and dependencies between affordances play a crucial role for action selection and behavior sculpting that goes beyond the present moment and allows planning into the future by chaining different affordances together. This ultimately results from the coordination of perception and the possibilities for action that a situation affords at a given time and place (Wells, 2002). For capturing this idea of a hierarchy among affordances coupled with the paradigm of behavior affording behavior (Gibson, 1977) in a relational manner, we introduce the relation Affords-Φ(Affords-φ 1 , Affords-φ 2 , .…”
Section: The Hierarchy Of Affordancesmentioning
confidence: 99%
“…It is important to understand that affordances are not merely properties of the environment: they exist only as a complementary relationship between an agent and its environment (Wells, 2002). Bucher and Helmond (2018) describe how the concept of affordances has been examined from different perspectives, such as high-level and low-level affordances (boyd, 2011), imagined affordances (Nagy & Neff, 2015), and vernacular affordances (Mcveigh-Schultz & Baym, 2015).…”
Section: Affordancesmentioning
confidence: 99%
“…Different researchers and scientists have defined affordance in their own terms and understanding as follows: Affordance is "Perception of the environment leads to a course of action" [3]; Affordance can be defined as "the actionable relation between the environment and an actor" (a person or animal or an object/artifact) [4]; "Affordances are properties of the environment taken relative to an observer." [5].…”
Section: Affordancementioning
confidence: 99%